PENGARUH FENOMENA ARAB SPRING TERHADAP KEBIJAKAN MENGENAI KETERSEDIAAN AKSES PENDIDIKAN PEREMPUAN DI ARAB SAUDI PADA PERIODE PEMERINTAHAN RAJA SALMAN TAHUN 2016-2020 - Lia Aulia, (2022)
The phenomenon of the Arab Spring which began in 2010 until mid-2011 as the beginning to forced for democracy organized by young activists against government in Saudi Arabia and the Middle East Countries. One of the interesting things that became the spotlight on the rise of democracy in the Middle East was the issue of women in the country. The issue of women's education began to surface since the presence of the Arab Spring phenomenon as the main factor that underlies the movement to demand a policy transition that is more pro-women so that this affects all aspects of life and socio-cultural order in the Middle East, especially during the reign of King Salman. The awareness of the government of the Kingdom of Saudi Arabia on the importance of the involvement of women and good use of human resources is a plan to advance the development of Saudi Arabia in the future. This makes Saudi Arabia gradually change its government system to be more prioritize the right to women's freedom, especially for women's access to education. This research was carried out with the aim of knowing whether the Arab Spring had an influence on women's education access policies and the initiation of the realization of Saudi Arabia's VISION 2030 which was considered a strategy to improve the positive image of Saudi Arabia in the wide world. The results of this study indicate that the influence of the Arab Spring phenomenon in Saudi Arabia can be said to be politically insignificant and does not have a major impact such as the phenomenon of regime overthrow in Middle Eastern countries. But the existence of the Arab Spring has quite an influence on social issues, regarding royal policies or government regulations in changing the social structure in Saudi Arabia. This began with the transfer of power from the previous regime, namely King Abdullah to King Salman and the appointment of the crown prince, Muhammad bin Salman in 2016-2017.